Fregean de re thoughts - Alves, Marco Aurélio Sousa (Cognitio-Estudos: revista eletrônica de filosofia, 2014)
This papers aims at clarifying some misunderstandings that seem to block an adequate account of de re thoughts within the Fregean framework. It is usually assumed that Fregean senses cannot be de re, or dependent upon objects. Contrary to this assumption, Gareth Evans and John McDowell have claimed that Fregean de re senses are not just possible, but in fact the most promising alternative for accounting for de re thoughts. The reasons blocking this alternative can be traced back to Russellian considerations that contaminated the interpretation of Frege. This contaminated understanding is first detected in Tyler Burge’s distinction between de dicto and de re, then connected to the motivations behind David Kaplan’s notion of character, and finally found in John Searle’s descriptivist account. The difficulty in understanding de re thoughts is, roughly speaking, a side effect of the misunderstanding of the boundaries separating internal and external elements of thoughts, as well as the distinction between mental content and means of representation.